Estudos de pré-formulação de cápsulas gelatinosas duras contendo formulação de extrato de Gymnema sylvestre em pó - Carbinatto, F. M. [UNESP] (2011)
Gymnema sylvestre extract (GSE) is a plant product widely used as an adjuvant in the treatment of diabetes mellitus and commercially available as a powder. Owing to its low flowability, the manufacturing of hard gelatin capsules containing GSE faces specific problems. The purpose of this study was to investigate the best excipient (starch, lactose or microcrystalline cellulose) for hard gelatin capsules containing GSE. The technological properties such us bulk density (ρβ); tapped density (ρt); inter-particle porosity (Ie); Carr index (CI); Hausner ratio (HR); loss on drying (%LOD) and particle size distribution (%Pf) of the various GSE mixtures were investigated with the aim of identifying the best excipient. The need for lubricants (talc/magnesium stearate) was also assessed. GSE was characterized as a fine powder with more than 50% of its particles between 0.149mm to 0.250mm; furthermore, CI=25.6%; RH=1.3 and Ie = 25.6% and, as expected with such properties, it showed poor flowability. All the excipients investigated were able to change the technological properties of GSE and the powder mixture containing microcrystalline cellulose gave the best results.